MASKULIN VALUES IN THE MODERN UZBEK MUSICAL INDUSTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article shows the reflection of the values, mood and character of the era in the culture of that time, in particular in the musical industry, using the example of an analysis of video clips of male singers. It also talks about the factors of the reflection of maskulin values in today's Uzbek society in the modern musical industry.